Main Character's Analysis of Social Conflict in the Movie "Agent Carter: Season 1" Christopher Markus Perspective - Razita, Raddin Putri; Habibullah, Mosleh; Ghofur, Abd.; Muthmainnah, Muthmainnah; Vargheese, KJ (International Journal of Education Research and Development, 2023)
This article aims to identify the social conflicts faced by the main character, explain the causes of the main character’s social and to analyze the solution to the main character’s social conflicts in the movie “Agent Carter Season 1”. Library research was used as the approach of this study, with data sources obtained through movie “Agent Carter Season 1” as the object of research. The researcher used the movie “Agent Carter Season 1” as primary data and obtained secondary data from several books, journals, internet sources, and other references. The results of this study indicate that the researcher found several social conflicts faced by Agent Carter, the main character in the movie. The social conflict that Agent Carter faced, such as conflict of interest, conflict of involving social position, and conflict of role. The researcher also found the causes of social conflicts faced by Agent Carter, namely differences between individuals, differences in interests, and social change. In addition, the researcher found problem-solving in social conflicts faced by Agent Carter, such as competing, collaborating, and compromising. It can be concluded that the researcher found three social matches faced by the main characters, three causes of social conflicts faced by the main characters, and three problems and solutions to social disputes faced by the main characters.